Thea Stilton and the Prince's Emerald - Stilton, Thea (New York : Scholastic Inc., 2012)
When the Thea Sisters' friend Ashvin is in trouble, they rush to his aid--in India! Ashvin has been working to return the monkeys living in the big city to their natural jungle environment. But the monkeys have suddenly started stealing jewels! Can the Thea Sisters figure out who is behind this terrible theft?
Original title: Lo smeraldo del principe indiano.
Translated from the Italian.
Ages 7-10.
Keywords: India -- Juvenile fiction. -- Mice -- Juvenile fiction. -- Monkeys -- Juvenile fiction. -- Theft -- Juvenile fiction